Female CEOs and investment efficiency in the Vietnamese market - SONG, Jun Myung (Institutional Knowledge at Singapore Management University, 2023)
This paper proposes female CEOs’ overconfidence and risky behavior stem from gender stereotype threats. With two subsamples in Vietnam—firms in the Northern and Southern regions–we empirically show that female CEOs in the North, where there is less gender stereotype, tend to overinvest relative to male CEOs. However, in the South, they are indifferent. Additional analysis reinforces the main finding that female CEOs from the North tend to take more risks even when dealing with market volatility and uncertainty (e.g., the COVID-19 pandemic). Such risky behaviors of female CEOs in the North do not deteriorate firm value but instead, possibly improve firm performance.